Comparative Anaesthetic Effects of Propofol and Tiletamine- Zolazepam Anaesthetic Agents in Dogs - Zalavadiya, Sunnykumar H; Vadalia, Jignesh V; Vagh, Arshi A; Bhatt, Raghuvir H; Talekar, Shivaji H; Dodia, Vaibhavsinh D; Bhesaniya, Monaliben B (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study evaluated two different anaesthetic protocols in dogs (n=24) for anaesthetic parameters like dose of anaesthetic agents for induction and maintenance of anaesthesia, quality of sedation, induction, maintenance of anaesthesia and recovery. All the animals were first premedicated with butorphanol @ 0.2 mg/kg b.wt. and xylazine @ 1 mg/kg b.wt., i/m, simultaneously. After 15 min of preanaesthetic medication, induction and maintenance of anaesthesia was achieved by administration of propofol @ 3 mg/kg b.wt., i/v in Group-I (n=12) and tiletamine-zolazepam @ 2 mg/kg b.wt., i/v in Group-II (n=12). Both protocols showed excellent quality of induction and maintenance of anaesthesia in the all animals. Physiological parameters like heart rate, respiration rate, rectal temperature and blood saturation of oxygen altered at different time intervals during the anaesthesia, but remained in normal physiological range. Xylazine and butorphanol preanesthetics showed dose sparing effect on induction and maintenance dose of propofol. Propofol resulted in excellent recovery quality and shorter recovery time compared to tiletamine-zolazepam.